2006
DOI: 10.1111/j.1440-1681.2006.04366.x
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Rat Aorta During Atherosclerosis Induced by High Cholesterol Diet and Injection of Vitamin D3

Abstract: 1. Atherosclerosis (AS) in rats displays important clinical similarities to human AS. 2. After the experimental model of AS in rat was established and using a proteomic approach, we compared the protein profiling of aorta tissues from healthy and AS rats. 3. Using two-dimensional electrophoresis (2-DE), over 1878 protein species were separated; among them, 1239 protein spots were matched between different gels with average matching rate of approximately 66%. Gel analysis and protein characterization have ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 16 publications
3
17
0
Order By: Relevance
“…Moreover, they have proven to be powerful tools in rodents studies for providing mechanistic insight into how vascular disease progresses and is influenced by environmental factors such as diet (Mayr et al 2005;Almofti et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they have proven to be powerful tools in rodents studies for providing mechanistic insight into how vascular disease progresses and is influenced by environmental factors such as diet (Mayr et al 2005;Almofti et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Adhesion molecules were analyzed in aortic lesions, which enhanced the intercellular adhesion of arteries in arteriosclerosis. The major receptors of lamin A were shown to be integrins and dystroglycan, which were also important in the inflammatory reactions during the development of diabetic arteriosclerosis (22). The results suggested that the inhibition effect of GSPE on lamin A at least partly contributed to the improvement of diabetic arteriosclerosis.…”
Section: Pimentioning
confidence: 62%
“…Usually the number of spots detected is very high and the more complicated the lesion is the higher the number of secreted proteins, suggesting that the production of specific proteins is related to the complexity of atherosclerotic lesion. Using 2D-gels analysis in an experimental model of atherosclerosis in rats (Almofti et al, 2006), found over 1898 protein species and 58 protein spots whose abundance was significantly altered in atherosclerotic animals. However this global approach does not generate specific information about the cell type involved or the correlation and sequence of events and signaling mechanisms between the partners involved in plaques progression.…”
Section: Proteomic Analysis Of Activated Endothelial Cellsmentioning
confidence: 99%